One‐pot three‐component reaction; synthesis of new symmetrically bridge 4, 4′‐(1, 4‐phenylene)di‐pyrimidines under solvent free conditions. (29th September 2021) - Mohamed, Asmaa H.; Abdelmeged, Hager S.; Shaker, Raafat M.; Abdel‐Latif, Fathy F.
Abstract: The present article describes a facile one‐pot synthesis of a new series of 4, 4′‐(1, 4‐phenylene)‐dipyrimidines (6a–c and 10a, b ) by the reaction of terephthalaldehyde (1 ), 2‐acetylthiophene, and/or nitriles with S‐benzylthiouronium chloride 3a . And also, the di‐pyrimidinones 13a‐d were obtained by the reaction of different amidines 3a–d and ethyl cyanoacetate (11 ) with terephthalaldehyde (1 ) under solvent‐free conditions in the existence of sodium hydroxide which is found to be a more efficient base for these reactions. The final products were characterized by spectral data and elemental analysis, IR, MS, 1 H, and 13 C NMR spectroscopy. Abstract : Synthesis of new di‐pyrimidine and di‐pyrimidinone compounds